Bicarbonate used as a buffer for controling nutrient solution pH value during the growth of hydroponic lettuce - Zhang, Mengxue; Wang, Wenxin; Zhong, Luming; Ji, Fang; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2024)
Unstable pH of nutrient solution in hydroponic systems is a major obstacle to production. To simplify the management of nutrient solution pH and attenuate negative effects of pH on plant growth, this study investigated the effect of different buffer salt additions on nutrient solution pH, ion uptake, growth and photosynthesis of Yamazaki lettuce, with the equivalent concentrations of macro-element unchanged. The results indicated that the pH of nutrient solution was buffered to varying degrees by the 2 mol/L HCO_3^-, 1 mol/L HCO_3^-, and 0.33 mol/L HPO_4^(2-) treatments. The 0.33 mol/L HPO_4^(2-) treatment fluctuated most with a pH of 1.74 units, while the addition of HCO_3^- buffered nutrient solution pH was better, with higher pH values (7.2-7.7). The CK-pH control solution, 1 mol/L HCO_3^- and 0.33 mol/L HPO_4^(2-) treatments all promoted the uptake of ion and then the growth of lettuce was better in comparison with the CK-pH no adjustment treatment, while the 2 mol/L HCO_3^- treatment inhibited K uptake and reduced the availability of Fe, the shoot and root fresh weight of lettuce decreased by 21.3% and 10.1%, respectively. In addition, although the chlorophyll content and net photosynthetic rate under 1 mol/L HCO_3^- and 0.33 mol/L HPO_4^(2-) treatments were significantly lower than the CK-pH control solution treatment, there were no significant differences in leaf length and leaf number of lettuce among them, and shoot fresh weight per plant was 83.09, 82.95, and 78.92 g, respectively. In conclusion, adding 1 mol/L HCO_3^- to the nutrient solution in a single dosage not only buffered the pH of nutrient solution better but also promoted ion uptake, it had no negative effects on the growth, photosynthesis and ion uptake of hydroponic lettuce in comparison with the CK-pH control solution treatment. Therefore, 1 mol/L HCO_3^- can be used as a buffer during the growth of hydroponic lettuce and reduce frequent addition of acids or alkalis, and then simplify the management of nutrient solution for hydroponic lettuce production. Keywords: pH buffer, nutrient solution, hydroponic lettuce, growth, ion uptakeDOI: 10.25165/j.ijabe.20241703.8692Citation: Zhang M X, Wang W X, Zhong L M, Ji F, He D X. Bicarbonate used as a buffer for controling nutrient solution pH value during the growth of hydroponic lettuce. Int J Agric & Biol Eng, 2024; 17(3): 59-67.